REVEGETATION EFFORTS AT FORMER MINING LAND IN CITATAH KARS AREA WEST BANDUNG REGENCY - hanna humaeriyah; sukron romadhona (UNEJ e-Proceeding, 2017)
Citatah karst area is the oldest kars in West Java that located in District Cipatat West Bandung Regency. Karst area in Cipatat District Gunung Masigit Village has 1,053 Ha area, one of the areas that have a potential of cultural heritage and geological reserves. Mining activities conducted in the kars area Citatah Gunung Masigit Village, in the form of active mining and post mining, resulting in decreased quality of physical, chemical, and biological soil fertility. To solve problems in post-mining areas, governments should be able to replace community livelihoods (such as limestone mining) to agriculture, farming, tourism and the creative economy. Through the efforts of plant revegetation. Several options plan that will be developed based on environmental, social, and economic conditions. Selection of plants for revegetation purposes, will be analyzed using Analytical Hierarcy Process (AHP), while to know the public response to revegetation and soil fertility assessment, will be analyzed descriptively. Based on the results obtained from the community response level, a positive response from the AHP analysis of the agrotourism revegetation program has a relative value of 0.834 states agreement for revegetation program with each positive response given that the most positive response is a conative response of 0.395, continued by cognitive response 0.277, affective response 0.199, while the relative value of the lowest response were shown in the negative response of 0.13. On the type of election plant revegetation, has acquired the plant revegetation well developed based on the relative value of the highest to the lowest of which is; 1). Corn (0.338 the highest crop species to be a revegetation commodity in both of social, economic and environmental conditions, 2). Guava (0,216), 3). Albasiah (0.109), 4). Cassava (0.084), 5). Soybean (0,043), 6) Cucumbers, Bananas, yam each have a relative value (0.042). Albasiah and nuts, can be used as pioneer plants to improve the fertility of the land before being developed in fruit and vegetable crops.